KEPUASAN PELANGGAN SATE TAICHAN GALAXY PRIOK - Dini Qotrun Nada (2020)
This research is a quantitative approach that aims to determine the effect of service quality and store atmosphere on customer satisfaction. The population in this study were all consumers of Sate Taichan Galaxy Priok in the North Jakarta Region. The sample size was taken as many as 50 respondents, with non-probability sampling method especially purposive sampling. Data collection was carried out by distributing questionnaires through google form to consumers of Sate Taichan Galaxy Priok. The data analysis technique used is descriptive analysis and inferential analysis with the help of SmartPLS 3.0 (Partial Least Square) software analysis tool. The results of this study indicate that service quality has a influence on customer satisfaction with a path coefficient of 0.863. While the store atmosphere has no influence on customer satisfaction with a path coefficient of -0.080.